Producción más limpia y sostenibilidad en la industria cosmética colombiana (2023)
For many years the cosmetics industry was considered one of the most polluting industries due to the raw materials used and production methods, for this reason it was forced to look for new alternatives to reduce the environmental impact and not disappear over the years. Cleaner production techniques and sustainability criteria have managed to position the industry positively again, reducing the pollution generated and providing additional benefits to the health of consumers. In Colombia the cosmetics industry is quite strong and growing more and more, which is why different environmentally friendly techniques have been implemented. Natural cosmetics have become trendy and have been chosen by different local businesses, since many consumers today seek to satisfy their needs, but are more aware of the origin of the products and the way in which they are made.